Construction and Radiolabeling of Adenovirus Variants that Incorporate Human Metallothionein into Protein IX for Analysis of Biodistribution - Lei Liu; Buck E. Rogers; Natalia Aladyshkina; Bing Cheng; Stephen J. Lokitz; David T. Curiel; J. Michael Mathis (Molecular Imaging)
Using adenovirus (Ad)-based vectors is a promising strategy for novel cancer treatments; however, current tracking approaches in vivo are limited. The C-terminus of the Ad minor capsid protein IX (pIX) can incorporate heterologous reporters to monitor biodistribution. We incorporated metallothionein (MT), a low-molecular-weight metal-binding protein, as a fusion to pIX. We previously demonstrated 99m Tc binding in vitro to a pIX-MT fusion on the Ad capsid. We investigated different fusions of MT within pIX to optimize functional display. We identified a dimeric MT construct fused to pIX that showed significantly increased radiolabeling capacity. After Ad radiolabeling, we characterized metal binding in vitro. We explored biodistribution in vivo in control mice, mice pretreated with warfarin, mice preimmunized with wild-type Ad, and mice that received both warfarin pretreatment and Ad preimmunization. Localization of activity to liver and bladder was seen, with activity detected in spleen, intestine, and kidneys. Afterwards, the mice were euthanized and selected organs were dissected for further analysis. Similar to the imaging results, most of the radioactivity was found in the liver, spleen, kidneys, and bladder, with significant differences between the groups observed in the liver. These results demonstrate this platform application for following Ad dissemination in vivo.